A Study of FDI in Service Sector of India - Kumar, Dinesh (Journal of Commerce and Trade, 2012)
In recent years, Foreign Direct Investments (FDI) have been playing an increasing role of enhancing the global competitiveness of firms of developing economies by providing access to strategic assets, technology, skills, natural resources and markets apart from enhancing south- south cooperation. The first decade of this century has also witnessed a number of emerging markets FDI is the key contributor for the enhancement of the industrial production, efficiency and productivity not only in developing countries but developed countries also. In India, it has been used as the vital tool for the upgradation of technological knowledge, competitiveness, know- how and managerial skills. The present paper is an attempt to analyze the significance of FDI in services sector in India after 1991.